2002
DOI: 10.1038/sj.gene.6363874
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen-activator-inhibitor-1 promoter polymorphism as a risk factor for adult periodontitis in non-smokers

Abstract: Periodontal diseases belong to the most common chronic disorders affecting mankind. Smoking and impaired plasminogen activation with hypercoagulation and fibrinolysis inhibition have been proposed as having a role in predisposition to these diseases. We investigated relationships among adult periodontitis, smoking, and a variation in the deletion/insertion (4G/5G) promoter polymorphism of the plasminogen-activator-inhibitor-1 (PAI-1) gene in 304 Caucasian subjects. An association was detected between the delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In the present study, although no statistically significant association was found between PAI-1 11560324 G > C and chronic periodontitis (Table 3), however, the trend is noteworthy. In a similar study, a significant association between polymorphisms in PAI-1 gene and chronic periodontitis in Czech population was reported by Holla et al 18 whereas Gurkan et al found no significant association of PAI-1 genotype and chronic periodontitis in Turkish population. 4 Here, we observed the presence of mutant (C) allele increased the risk, and severity of periodontitis.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the present study, although no statistically significant association was found between PAI-1 11560324 G > C and chronic periodontitis (Table 3), however, the trend is noteworthy. In a similar study, a significant association between polymorphisms in PAI-1 gene and chronic periodontitis in Czech population was reported by Holla et al 18 whereas Gurkan et al found no significant association of PAI-1 genotype and chronic periodontitis in Turkish population. 4 Here, we observed the presence of mutant (C) allele increased the risk, and severity of periodontitis.…”
Section: Discussionsupporting
confidence: 65%
“…[9][10][11][12][13] Studies have reported a 4 G/5G promoter polymorphism of PAI-1 gene to be linked with a disease like Chronic Heart Disease, [14][15][16] meningococcal septic shock 17 and periodontal disease. 18 The study was performed to explore the relation between Single Nucleotide Polymorphisms (SNPs) of PAI-1 gene (rs 11560324) with chronic periodontitis and alveolar bone loss severity involved in chronic periodontitis in North Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…The association between 1G/2G polymorphism and chronic periodontitis was observed most strongly in non‐smoking, and not in smoking subjects. We have shown in another study (Izakovicova Holla et al 2002a) that genetic susceptibility to periodontitis can easily be evincible in non‐smokers because degradation of connective tissues in smokers may occur as a consequence of smoking, thus possibly masking the influence of individual variants of the MMP‐1 polymorphisms. Furthermore, the frequency of 1G/1G homozygotes in a subgroup of severe periodontitis non‐smoking patients (40.4%) was increased in relation to non‐smoking controls (29.8%), and also in comparison with smoking patients (30.4%) or smoking healthy subjects (30.9%), but it was similar to frequency of the 1G/1G genotype in mild/moderate non‐smoking periodontitis patients (42.5%).…”
Section: Discussionmentioning
confidence: 96%
“… cytokines (3, 5, 7, 10, 12, 13, 17, 18, 20, 23, 25, 27, 29–32, 38–40, 42–46, 52, 54, 58, 59, 61, 71, 73, 76, 84–89, 93, 94, 97–99, 101, 109–113, 115, 120, 122, 124–127, 129, 131–134, 144, 149, 150, 152, 154); HLA (1, 2, 4, 8, 15, 28, 33, 55, 56, 68, 77, 92, 103, 105, 106, 108, 117, 135, 145, 147); immuno‐receptors (14, 16, 34–36, 47, 57, 72, 78–82, 91, 95, 136, 137, 153, 155–157); proteases (24, 26, 60, 62, 66, 67); structural molecules (19, 21, 22, 48, 49, 51, 53, 64, 138, 142, 143, 148); others (9, 37, 50, 63, 74, 83, 90, 96, 100, 121, 128, 139, 140, 158, 159). …”
Section: Single Nucleotide Polymorphisms In Periodontal Diseasementioning
confidence: 99%